Condenação de pés por artrite em aves abatidas na região norte do Paraná: incidência e pesquisa de infecção bacteriana - Barbosa, Liria Paula de Camargo (2024)
Brazil is the second largest poultry producer in the world, behind only the United States. The poultry sector has become highly competitive in the animal products market, due to the fast production cycle and low production cost. During the slaughter process, the carcasses are inspected in accordance with the criteria stipulated by the Federal Inspection Service (SIF), through ante mortem and post mortem evaluations. Among the possible causes of condemnations is arthritis, a locomotor problem that hinders the mobility of poultry, causing losses in production and economic losses for companies. Infectious arthritis can be viral or bacterial, and manifests itself visually through different degrees of joint damage. This study aimed to investigate the incidence of condemnation of poultry feet due to arthritis in a slaughterhouse located in the northern region of Paraná and to research the frequency of bacterial infection in the condemned joints, over a period of 12 months. The study was conducted by surveying joints condemned by arthritis from the Cobb and Ross strains from three different producers, followed by classifying the severity of the lesions by macroscopic visualization. A total of 30 condemned joint samples, 10 classified as mild, 10 moderate and 10 severe, were analyzed for the presence of bacteria and subjected to histopathological analysis. Of the total of 15,497,842 poultry feet analyzed by the Federal Inspection Service, 127,314 (0.82%) were condemned due to arthritis in the joints. Analyzing the incidence of rejection in relation to poultry lines, 81,535 (64.04%) belonged to the Cobb lineage, while 45,779 (35.96%) belonged to the Ross lineage. The conviction rate among producers ranged from 0.7 to 1.0% (p > 0.05). The conviction rate between the Cobb (0.7%) and Ross (1.4%) lines was also not significant. The average conviction rate over the months of the study ranged from 0.41 to 3.59%, with a higher incidence in the month of May. The average conviction rate throughout the climatic seasons ranged from 0.6% to 1.8%, with autumn being statistically higher than in other seasons. Of the total of 30 samples of condemned joints analyzed, 27 (90%) showed some bacterial infection, with E. coli predominating at all levels of injury, followed by Staphylococcus aureus, Enterococcus sp., Pantoea agglomerans and Providencia stuartii. In the histopathological examination, 13 (43.33%) presented heterophilic inflammatory infiltrate compatible with viral and bacterial infection, 3 in samples of moderate degree and 10 in samples classified as severe. In healthy joint samples (control) and classified as mild, no heterophilic inflammatory infiltrate was observed. The results indicate that there was bacterial growth in samples collected from the joints of poultry condemned by the federal inspection service, suggesting that inflammation in the joints may be of bacterial origin. The recognition of microorganisms makes it possible to implement preventive and control measures on poultry farms, as it contributes to a reduction in poultry treatment costs and greater use of the final product, with a view to reducing losses and economic losses for the companies.